Application of Titanium Dioxide-Graphene Composite Material for Photocatalytic Degradation of Alkylphenols. (15th August 2012) - Basheer, Chanbasha
Abstract : Titanium dioxide-graphene (TiO2 -G) composite was used for the photodegradation of alkylphenols in wastewater samples. The TiO2 -G composites were prepared via sonochemical and calcination methods. The synthesized composite was characterized by X-ray diffraction (XRD), infrared spectroscopy (IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX), and fluorescence spectroscopy. The photocatalytic efficiency was evaluated by studying the degradation profiles of alkylphenols using gas chromatography-flame ionization detector (GC-FID). It was found that the synthesized TiO2 -G composites exhibit enhanced photocatalytic efficiencies as compared to pristine TiO2 . The presence of graphene not only provides a large surface area support for the TiO2 photocatalyst, but also stabilizes charge separation by trapping electrons transferred from TiO2, thereby hindering charge transfer and enhancing its photocatalytic efficiency.